Co-gasification of high ash biomass and high ash coal in downdraft gasifier. (February 2019) - Thengane, Sonal K.; Gupta, Ankita; Mahajani, Sanjay M.
Graphical abstract: Highlights: High ash biomass and coal are processed successfully in improvised downdraft gasifier. CO2 char gasification is studied on TGA to confirm the effect of inorganic content. Biomass ratio of 0.75 was found to be optimal in terms of gas calorific value and CGE. Different factors contributing to enhanced performance of BR 0.75 case investigated. Preliminary atmospheric emissions and particulates values are found to be acceptable. Abstract: The present work studies gasification of high ash biomass (20–25% w/w), high ash coal (30–35% w/w), and their co-gasification in a downdraft gasifier developed in our earlier study (Siddiqui et al., 2018). TGA studies were performed to examine the change in performance due to the catalytic effect of inorganic content. The effect of biomass ratio (BR) was examined. Higher percentage of biomass increased the conversion to gas on carbon basis, and decreased the conversions to char and tar. The presence of coal enhanced the temperature and hence the rates of the reactions to certain extent. The respective cold gas and thermal efficiencies for BR0 are 33.06% and 49.38%, and for BR1 are 52.22% and 64.15%. BR0.75 gave the best performance with CGE of 57.5% and thermal efficiency of 72.63%. Finally, the clinker formation issue and the preliminary atmospheric emissions measurements are reported for gasifier.